2007
DOI: 10.1364/oe.15.000992
|View full text |Cite
|
Sign up to set email alerts
|

Visible laser emission of solid state pumped LiLuF4:Pr3+

Abstract: In the present work we report on the growth, spectroscopy and laser results of LiLuF(4):Pr(3+) 1.25% in the melt. Room temperature polarized absorption and emission spectra have been recorded and the decay time of the (3)P0 manifold has been measured. Finally efficient room temperature laser emission have been obtained at 522.8 nm, 607.25 nm, 640.17 nm and 721.5 nm under 480 nm pumping by means of an optically pumped semiconductor laser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(36 citation statements)
references
References 0 publications
2
33
1
Order By: Relevance
“…It can be found that the peak emission cross-sections of the 3 P 0 → 3 F 2 as red laser channel is 3.27 × 10 −20 cm 2 , and this band has the largest emission cross-sections among all the emission bands of Pr:GGG crystal. While the emission cross-sections of 1.25% Pr 3+ -doped LiLuF 4 crystal at 640.2 nm is 2.2 × 10 −19 cm 2 , in which a red laser has been achieved [10]. As we conceive, if Ce 3+ or other ions is co-doped into Pr:GGG crystal, direct and trap mediated capture and recombination of holes and electrons via Pr 3+ and Ce 3+ or other ions might provide the larger photon production in GGG crystals, and help to increase the emission intensity and cross-sections of visible bands.…”
Section: Fluorescence Spectroscopy and Stimulated Emission Cross-sectmentioning
confidence: 96%
See 2 more Smart Citations
“…It can be found that the peak emission cross-sections of the 3 P 0 → 3 F 2 as red laser channel is 3.27 × 10 −20 cm 2 , and this band has the largest emission cross-sections among all the emission bands of Pr:GGG crystal. While the emission cross-sections of 1.25% Pr 3+ -doped LiLuF 4 crystal at 640.2 nm is 2.2 × 10 −19 cm 2 , in which a red laser has been achieved [10]. As we conceive, if Ce 3+ or other ions is co-doped into Pr:GGG crystal, direct and trap mediated capture and recombination of holes and electrons via Pr 3+ and Ce 3+ or other ions might provide the larger photon production in GGG crystals, and help to increase the emission intensity and cross-sections of visible bands.…”
Section: Fluorescence Spectroscopy and Stimulated Emission Cross-sectmentioning
confidence: 96%
“…Recently the spectroscopic properties of Pr 3+ ion have been investigated extensively in various hosts including single crystals [1][2][3], nanocrystals [4], powders [5][6][7][8], glasses [9], etc. When the Pr 3+ ions are pumped to the closely grouped 3 P J (J = 0, 1, 2) multiplets, several emissions in red ( 3 P 0 → 3 F 2 ), deep red ( 3 P 0 → 3 F 4 ), orange ( 3 P 0 → 3 H 6 ), green ( 3 P 1 → 3 H 5 ), and blue ( 3 P 0 → 3 H 4 ) spectral regions have been demonstrated in tungstate [6], vanadate phosphors [8], molybdate [3], fluoride crystals [1,10], etc. Also, two dominant transitions from the fluorescent 3 P 0 level of Pr 3+ to the lower 3 H 6 and 3 H 4 states can be mixed to give out white light for application to white LEDs [11].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…One of the most promising candidates within the rare earth ions is trivalent praseodymium (Pr 3 þ ), offering several transitions with high cross sections in the visible spectral regions. During the past decade, efficient cw single wavelength laser for different transitions of Pr 3 þ have been demonstrated for some crystals such as Pr 3 þ :LiYF 4 [47][48][49][50][51][52][53][54], Pr 3 þ :LiLuF 4 [55][56][57][58], Pr 3 þ :KY 3 F 10 [59,60], and Pr 3 þ :LiGdF 4 [61]. However, simultaneous dual-wavelength laser in the visible spectral range can find wide applications in many fields such as display technology, spectral analysis, medical applications, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The emission wavelength of these devices around 445nm matches nicely the absorption of the Pr 3+-ion . Several recent publications [2][3][4][5] have reported output power levels from GaN-diode pumped Pr-lasers in the order of 30-50m W, which is still too low for the compact projectors mentioned above. In this paper we report the results of our work towards higher output power from these devices .…”
mentioning
confidence: 99%